A Comparative Analysis Of Mood And Modality In Report Texts: Student Vs. Textbook Models - Nur Aziza, Maulida; Setyarini, Sri; Gunawan, Wawan (Doctoral Program of Social Science Pasundan University, 2025)
This study examines mood and modality in report texts, comparing student-generated writing with a textbook model to explore how these linguistic features construct interpersonal meaning. Using the framework of Systemic Functional Linguistics, the analysis focuses on mood types (declarative, interrogative, imperative) and modality expressions (probability, obligation) to identify patterns and discrepancies between the two text types. The findings reveal that both texts predominantly utilize declarative moods, reflecting the genre's objective of presenting factual information. However, the textbook model demonstrates greater grammatical accuracy and linguistic precision, while the student text shows variability and frequent errors in mood realization. In terms of modality, the textbook employs a balanced range of modal verbs to express nuanced attitudes and probabilities, contributing to its authoritative tone. Conversely, the student text relies heavily on basic modal verbs like *will*, limiting its ability to convey complex interpersonal meanings. These differences highlight a significant gap between textbook standards and student writing practices, suggesting the need for explicit instruction on mood and modality to enhance students' academic writing skills. This study underscores the importance of integrating targeted pedagogical strategies that address both grammatical proficiency and genre awareness. By bridging the gap between idealized models and student performance, educators can better support learners in mastering the linguistic features essential for effective report writing. The findings contribute to understanding how mood and modality operate within educational texts and offer insights for improving teaching practices in language education.